Q: What is the square root of 8x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

√(10x) * √(8x) = √(80x²)√(80x²) = √(16x²) * √(5) = 4x*√(5)■

x = 8

x2 + 8x + 5 = 0 is an expression, not a value, and thus does not actually have a square root. If you are looking to solve for x, then you can say: x2 + 8x + 5 = 0 ∴ x2 + 8x + 16 = 11 ∴ (x + 4)2 = 11 ∴ x + 4 = ±√11 ∴ x = 4 ±√11

4x-8x = -4x √-4x stands. However, x could not possibly be a positive number, because: (Negative) X (Positive) = (Negative) The square root of a negative number is undefined-so... (√-4x) + 9 Is your answer.

Which inequality represents all values of x for which the quotient below is defined?square root of 28(x-1) divided by square root of 8x^2

Related questions

√(10x) * √(8x) = √(80x²)√(80x²) = √(16x²) * √(5) = 4x*√(5)■

x = 8

sqrt(10x)*sqrt(8x) = sqrt(80x2) = sqrt(16x2*5) = sqrt(16x2)*sqrt(5) = 4x*sqrt(5)

if you mean X²+8X-5=0: X1=-8/2 - Square root of ((8/2)²+5) X1=-4 - Square root of 21 X1 is about -8.58 X2=-8/2 + Square root of ((8/2)²+5) X2=-4 + Square root of 21 X2 is about 0.58

x2 + 8x + 5 = 0 is an expression, not a value, and thus does not actually have a square root. If you are looking to solve for x, then you can say: x2 + 8x + 5 = 0 ∴ x2 + 8x + 16 = 11 ∴ (x + 4)2 = 11 ∴ x + 4 = ±√11 ∴ x = 4 ±√11

y=(8x).5 + (4x).5 = (2+2sqrt(2))x.5 y'=(1 + sqrt(2))/sqrt(x)

4x-8x = -4x √-4x stands. However, x could not possibly be a positive number, because: (Negative) X (Positive) = (Negative) The square root of a negative number is undefined-so... (√-4x) + 9 Is your answer.

Let's x be one of the numbers, and y the other number. So, x + y = -8 xy = 6 y = -x - 8 x(-x -8) = 6 -x^2 - 8x = 6 multiply by -1 both sides x^2 + 8x = -6 solve for x by completing the square; x^2 + 8x + 16 = -6 + 16 (x + 4)^2 = 10 x + 4 = square root of 10 x = -4 + square root of 10 or x = -4 - square root of 10 if we continue to solve the system of the equations, we can find the same value for y. Thus the numbers are -4 + square root of 10 and -4 - square root of 10. Check: (-4 + square root of 10) + (-4 - square root of 10) = -4 + square root of 10 - 4 - square root of 10 = -8 (-4 + square root of 10)(-4 - square root of 10) = (-4)^2 - (square root of 10)^2 = 16 - 10 = 6

The square root of the left hand side is 2*(x - 1).The square root of the right hand side is 2*sqrt(14)

23

the answer of √8x+16-3x=0 is x= 0.447213595 = +/- 0.447(to 3 decimal places) if I'm not mistaken

Which inequality represents all values of x for which the quotient below is defined?square root of 28(x-1) divided by square root of 8x^2